Multi‐Pyrene Assemblies Supported on Stannoxane Frameworks: Synthesis, Structure and Photophysical Studies. Issue 5 (11th March 2014) - Kundu, Subrata; Metre, Ramesh K.; Yadav, Rajeev; Sen, Pratik; Chandrasekhar , Vadapalli
Abstract Organostannoxanes have been used as scaffolds for the preparation of multi‐chromophore assemblies. A single‐step synthesis procedure allows the preparation of compounds in which the number of chromophore units can be varied from two to six. Thus, the reactions of pyrene sulfonic acid (PySO3H) or C16H9CHNC6H3(COOH)2 (LH2) with various organotin precursors gave pyrene‐containing organostannoxanes, that is, [Ph3SnPySO3]6 (1), [{(Me2Sn)2(μ3‐O)(μ‐OH)PySO3}2{(Me2Sn)2(μ3‐O)(μ‐OH)H2O}2⋅2 PySO3] (2), [{tBu2Sn(OH)PySO3}2] (3), [{(nBuSn)12(O)14(OH)6{PySO3}2] (4), and [{(nBu2Sn)L}3]2⋅C6H5CH3 (5). Compounds 1–5 were characterized by using X‐ray crystallography. Compounds 1 and 5 are 24‐membered macrocycles. Macrocycle 1 possesses intramolecular π–π stacking interactions. An unusual co‐crystal of two tetrameric ladders in 2 was observed in which one of the components of the co‐crystal is neutral whereas the other is dicationic and two pyrenesulfonate counterions are present to balance the overall charge. In the solid state these compounds reveal rich supramolecular structures. Photophysical studies on 1–5 reveal that interactions in the solid state lead to considerable broadening of the emission bands.